2011
DOI: 10.1021/jp205343r
|View full text |Cite
|
Sign up to set email alerts
|

Local Oxidation of Polystyrene by Scanning Electrochemical Microscopy

Abstract: ACKNOWLEDGMENTThe "Agence Nationale de la Recherche" is gratefully acknowledged for its financial support via the ANR-06-BLAN-0368 project.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 47 publications
0
18
0
1
Order By: Relevance
“…, which can be easily produced in a friendly environment, SECM has been used to pattern different organic layers immobilized on various substrates by generating HO . from the Fenton reaction, by electrogenerating Ag 2+ , or by taking advantage of the specific properties of platinum …”
Section: Introductionmentioning
confidence: 94%
“…, which can be easily produced in a friendly environment, SECM has been used to pattern different organic layers immobilized on various substrates by generating HO . from the Fenton reaction, by electrogenerating Ag 2+ , or by taking advantage of the specific properties of platinum …”
Section: Introductionmentioning
confidence: 94%
“…Possible pathways of the silver reduction could thus be: autocatalytic light reduction [16] (although we tried to work in the dark as much as possible); reduction in contact with air/water; incomplete sulfonation of the polymer with remaining polystyrene groups, the latter of which can be oxidized [17]. The chemical reduction of the silver ions in the PSSAg nanocomposite by adding ascorbic acid yields silver nanoparticles of 160 AE 38 nm on average.…”
Section: Complexation Of Pss With Silver Oxidementioning
confidence: 99%
“…[6,12] The pH shift associated with nitrite oxidation was applied in the local etching of a thin Ni coating on a gold substrate in a chemical lens. [13] Kanoufi et al reported the localized reduction of poly(tetrafluoroethylene) [14] and the oxidation of polystyrene [15] followed by further surface treatments. More recently, Hapiot et al discovered that transient hydroxyl radicals OHC can be used to remove organic coatings.…”
mentioning
confidence: 99%